2013
DOI: 10.37543/oceanides.v28i1.120
|View full text |Cite
|
Sign up to set email alerts
|

First record of a red tide caused by Gyrodinium instriatum (Dinophyceae: Gymnodiniales) in Bahía de Acapulco, Guerrero

Abstract: Primer registro de una marea roja ocasionada por Gyrodinium instriatum (Dinophyceae: Gymnodiniales) en Bahía de Acapulco, Guerrero El 26 de Enero de 2012 se observó en la Bahía de Acapulco una marea roja causada por el dinoflagelado desnudo Gyrodinium instriatum, cuya abundancia varió entre 796 y 2120 × 103 céls L–1. Otros dinoflagelados abundantes fueron Noctiluca scintillans y Gymnodinium catenatum. Los valores promedio de temperatura y salinidad (in situ) fueron de 24.4 °C y 33.13, respectivamente durante … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Phytoplankton sequence data showed dissimilarities between the two lagoons, where Marchica was dominated by dinoflagellates and Oualidia by Ochrophytes and Chlorophytes. The red dinoflagellate Gyrodinium Hulbert belongs to the family Dinophyceae, which lack armor protists responsible for red tides [83]. The Ochrophyta genus Pseudo-Nitzschia Peragallo, which belongs to diatoms, is responsible for amnesic shellfish poisoning (ASP); blooms were observed globally in coastal waters and were linked to elevated nutrient concentrations in marine environments [76].…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton sequence data showed dissimilarities between the two lagoons, where Marchica was dominated by dinoflagellates and Oualidia by Ochrophytes and Chlorophytes. The red dinoflagellate Gyrodinium Hulbert belongs to the family Dinophyceae, which lack armor protists responsible for red tides [83]. The Ochrophyta genus Pseudo-Nitzschia Peragallo, which belongs to diatoms, is responsible for amnesic shellfish poisoning (ASP); blooms were observed globally in coastal waters and were linked to elevated nutrient concentrations in marine environments [76].…”
Section: Discussionmentioning
confidence: 99%
“…Except for the model diatom Phaeodactylum tricornutum, the other four were reported as bloom species elsewhere (Shikata et al, 2008;Begum et al, 2015;Tse and Lo, 2017;. L. fissa blooms are frequent in the Pearl River Estuary, while the phenomenon is not common worldwide (Jimeneź, 1993;Nagasoe et al, 2006;Nagasoe et al, 2010;Gaŕate-Lizaŕraga et al, 2013). L. fissa showed few advantages in interspecific competition with three other algal bloom-forming species, Skeletonema dohrnii (Bacillariophyceae), Prorocentrum micans (Dinophyceae), and Chattonella marina (Raphidophyceae), using pure, sterilized cultures in previous research .…”
Section: Discussionmentioning
confidence: 99%
“…Levanderina fissa (formerly Gyrodinium instriatum) has frequently caused blooms in the Pearl River Estuary in the past two decades, for example, blooms in Shenzhen Bay in 1998Zhu et al, 2004;SOA, 2008); Lingding Bay in 2002 (Wang et al, 2003); and Zhuhai coastal waters in 2009 . However, blooms caused by this species elsewhere were rare and were observed only in the Gulf of Guayaquil in Ecuador (Jimeneź, 1993); Hakozaki Fishing Port of Japan (Nagasoe et al, 2006;Nagasoe et al, 2010); and Bahia de Acapulco, Mexico (Gaŕate-Lizaŕraga et al, 2013). Our previous study showed that L. fissa had few advantages in interspecific competition with three other algal bloom-forming species, namely, Skeletonema dohrnii (Bacillariophyceae), Prorocentrum micans (Dinophyceae), and Chattonella marina (Raphidophyceae), using pure, sterilized cultures .…”
Section: Introductionmentioning
confidence: 99%
“…Except for the model diatom Phaeodactylum tricornutum, the other four were reported as bloom species elsewhere (Shikata et al, 2008;Begum et al, 2015;Tse and Lo, 2017;Li et al, 2019). L. fissa blooms are frequent in the Pearl River Estuary, while the phenomenon is not common worldwide (Jimeneź, 1993;Nagasoe et al, 2006;Nagasoe et al, 2010;Gaŕate-Lizaŕraga et al, 2013). L. fissa showed few advantages in interspecific competition with three other algal bloom-forming species, Skeletonema dohrnii (Bacillariophyceae), Prorocentrum micans (Dinophyceae), and Chattonella marina (Raphidophyceae), using pure, sterilized cultures in previous research (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Levanderina fissa (formerly Gyrodinium instriatum) has frequently caused blooms in the Pearl River Estuary in the past two decades, for example, blooms in Shenzhen Bay in 1998, 2003(Wang et al, 2001Zhu et al, 2004;SOA, 2008); Lingding Bay in 2002 (Wang et al, 2003); and Zhuhai coastal waters in 2009 (Wang et al, 2011). However, blooms caused by this species elsewhere were rare and were observed only in the Gulf of Guayaquil in Ecuador (Jimeneź, 1993); Hakozaki Fishing Port of Japan (Nagasoe et al, 2006;Nagasoe et al, 2010); and Bahia de Acapulco, Mexico (Gaŕate-Lizaŕraga et al, 2013). Our previous study showed that L. fissa had few advantages in interspecific competition with three other algal bloom-forming species, namely, Skeletonema dohrnii (Bacillariophyceae), Prorocentrum micans (Dinophyceae), and Chattonella marina (Raphidophyceae), using pure, sterilized cultures (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%